Clinically Integrated Molecular Diagnostics in Adenoid Cystic Carcinoma. (29th March 2019) - Thierauf, Julia; Ramamurthy, Nisha; Jo, Vickie Y.; Robinson, Hayley; Frazier, Ryan P.; Gonzalez, Jonathan; Pacula, Maciej; Dominguez Meneses, Enrique; Nose, Vania; Nardi, Valentina; Dias‐Santagata, Dora; Le, Long P.; et al.
Abstract: Background: Adenoid cystic carcinoma (ACC) is an aggressive salivary gland malignancy without effective systemic therapies. Delineation of molecular profiles in ACC has led to an increased number of biomarker‐stratified clinical trials; however, the clinical utility and U.S.‐centric financial sustainability of integrated next‐generation sequencing (NGS) in routine practice has, to our knowledge, not been assessed. Materials and Methods: In our practice, NGS genotyping was implemented at the discretion of the primary clinician. We combined NGS‐based mutation and fusion detection, with MYB break‐apart fluorescent in situ hybridization (FISH) and MYB immunohistochemistry. Utility was defined as the fraction of patients with tumors harboring alterations that are potentially amenable to targeted therapies. Financial sustainability was assessed using the fraction of global reimbursement. Results: Among 181 consecutive ACC cases (2011–2018), prospective genotyping was performed in 11% ( n = 20/181; n = 8 nonresectable). Testing identified 5/20 (25%) NOTCH1 aberrations, 6/20 (30%) MYB‐NFIB fusions (all confirmed by FISH), and 2/20 (10%) MYBL1‐NFIB fusions. Overall, these three alterations (MYB/MYBL1/NOTCH1) made up 65% of patients, and this subset had a more aggressive course with significantly shorter progression‐free survival. In 75% ( n = 6/8) of nonresectable patients, we detected potentially actionable alterations. Financial analysis of the global charges, including NGS codes, indicated 63% reimbursement, which is in line with national (U.S.‐based) and international levels of reimbursement. Conclusion: Prospective routine clinical genotyping in ACC can identify clinically relevant subsets of patients and is approaching financial sustainability. Demonstrating clinical utility and financial sustainability in an orphan disease (ACC) requires a multiyear and multidimensional program. Implications for Practice: Delineation of molecular profiles in adenoid cystic carcinoma (ACC) has been accomplished in the research setting; however, the ability to identify relevant patient subsets in clinical practice has not been assessed. This work presents an approach to perform integrated molecular genotyping of patients with ACC with nonresectable, recurrent, or systemic disease. It was determined that 75% of nonresectable patients harbor potentially actionable alterations and that 63% of charges are reimbursed. This report outlines that orphan diseases such as ACC require a multiyear, multidimensional program to demonstrate utility in clinical practice. Abstract : Adenoid cystic carcinoma is a rare but aggressive type of salivary gland malignancy. This article addresses the need for more effective, biomarker‐informed therapies in rare cancers, focusing on clinical utility and financial sustainability of integrated next‐generation sequencing in routine practice.